Penguasaan Tangga Nada Bagi Pelajar Kelas X SMAN Benlutu Melalui Latihan Bermain Pianika - Nidarwan Ranboki, Richard; Petrus Olin, Mario; Ursula Jawa Mukin, Maria (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
KKN is a form of implementation of the dharma of service that provides work and learning experience for students in community empowerment. One form of activity in the KKN program is training activities to master scales for students of Class X SMA N Benlutu through pianika playing exercises. This activity aims to make students know how to operate the pianika musical instrument. The stages of service implementation began with observation, core activities of introducing the pianika instrument and documentation. Based on the results of observations and interviews, one of the factors causing the low ability to play the pianika instrument is the absence of a music teacher so that the art subject teacher teaches music. In addition, the lack of teacher knowledge about music learning is because teachers are more dominant in providing information than implementing learning through practice or training. The results of this training showed an improvement in the participants' ability to master scales in music. The participants also showed a greater love and interest in music, as well as a passion to continue learning and developing their skills in music. This training activity is expected to be one of the efforts to increase interest and achievement in music, especially among SMA N Benlutu students